REQUIREMENTS MANAGEMENT TOOL ELEMENTS FOR THE MALAYSIAN SOFTWARE INDUSTRY (Journal of Information and Communication Technology, 2012)
Developing quality software is becoming a challenge that requires the practitioners to employ appropriate techniques, methodologies and good practices in software engineering. In the Malaysian software industry, the challenges are the practitioners lack practice in software engineering especially in the requirements management practices, and the requirements management tool is not widely facilitated during software development projects. In order to encourage them to overcome these problems, this paper attempts to recommend a requirements management tool that embeds the best practices in managing requirements. In addition, this paper aims to investigate the elements of the tool to guarantee that the tool is appropriate for Malaysian software needs. Then, a comparative study is carried out to search for various available requirements management tools that have those elements. The results show that there is no specific tool that has all the elements to fit the Malaysian software needs. Therefore, it is essential to develop a requirements management tool that is able to assist the software practitioners in developing quality software.